Reduced cortical volume of the default mode network in adolescents with generalized anxiety disorder. Issue 6 (21st March 2022) - Bashford‐Largo, Johannah; Zhang, Ru; Mathur, Avantika; Elowsky, Jaimie; Schwartz, Amanda; Dobbertin, Matthew; Blair, Robert James R.; Blair, Karina S.; Bajaj, Sahil
Abstract: Background: Widespread structural alterations have been shown to be implicated in individuals with generalized anxiety disorder (GAD). However, there have been inconsistent findings in cortical volume (CV) differences. Most structural neuroimaging studies looking at GAD used region‐based approach with relatively small sample sizes, let alone be specific to adolescents with GAD. We believe this is the first study to look at CV measures using a network‐based approach in a larger sample of adolescents with GAD. The goal of the current study was to focus on three different brain networks (i.e., Limbic, Frontoparietal, and Default Mode Network [DMN]) in adolescents with GAD. Method: The study involved 81 adolescents with GAD and 112 typically developing (TD) comparison individuals matched on age (15.98 and 15.63 respective means), sex (42F/39M and 45F/67M), and IQ (101.90 and 103.94 respective means). Participants underwent structural MRI. Freesurfer was used to estimate CV (both network‐specific and region‐specific within networks) and region‐specific sub‐cortical volume measures. Multivariate analysis of covariance (MANCOVA; with sex, age, IQ, and intracranial volume [ICV] as potential covariates) was used to estimate group differences. Results: We found significantly lower CV for the DMN in adolescents with GAD, compared with TD individuals. Adolescents with GAD also showed significantly lower hemispheric mean CV of the default‐mode regions (particularly the prefrontal and temporal regions) and the hippocampus, compared with TD individuals. Conclusion: The current findings suggest structural alterations in adolescents with GAD. These structural alterations will need to be addressed when implementing and developing treatments for patients with GAD.